Cholesterol levels: the prognostic significance in ICU patients - A., Jeyasuriya; A. K., Badrinath; Nagalingam, Saranya (International Journal of Advances in Medicine, 2018)
Background: The aims of the study were to monitor the total cholesterol levels at different time intervals in ICU patients and to analogize the values with the outcome of disease, to study the prevalence of hypocholesterolemia among ICU patients and to assess the trend of hypocholesterolemia among various diseases. Methods: Present study populace consists of 55 patients admitted in ICU. For these patients, lipid profile was done on the day of admission and day-3 of admission. The total cholesterol levels done on day 1 and 3 were compared with disease outcome. Results: The mean cholesterol value among 33 survivors on day 1 was 120.76(±18.54) and day 3 was 145.30 (±55.65) with p value of 0.019, that is statistically significant. As the total cholesterol value increases during the period of ICU stay, it proves to be an early prognostic indicator of disease outcome. The patients showing increasing trend of total cholesterol levels has increased chances of survival. Similarly, HDL value among 33 survivors on day 1 was 31.70 (±3.98) and day 3 was 36.39 (±11.98), with p value of 0.033, that is statistically significant and also, the mean LDL value among 33 survivors on day 1 was 68.25 (±17.14) and day 3 was 78.78 (±24.74), with p value of 0.009, which was also found to be statistically significant. The mean cholesterol value among 22 non-survivors on day 1 was 131.64 (±15.24) and day 3 was 122.09 (±26.23), the mean HDL among 22 non-survivors on day 1 was 33.14 (±3.79) and day 3 was 31.32 (±4.23). Conclusions: Present study’s intend of monitoring the total cholesterol level was successfully demonstrated that it can be used as prognostic tool in ICU patients. The increasing trend in total cholesterol level indicates better prognosis of disease outcome. Similarly, the increasing trend in HDL and LDL levels also can be used as prognostic tool to determine the survival rate of patient.